Terapi Aktivitas Kelompok (TAK) Terapi Tertawa, Mendengarkan Musik Sambil Menebak Gambar pada Lansia (Lembaga Pengembangan Kinerja Dosen, 2026)
The elderly are a vulnerable group to experience decreased physical and cognitive function, such as hypertension and dementia, which can affect their quality of life. The Activity Therapy Program aims to improve the well-being of the elderly through laughter therapy, listening to music, and playing guess the word. The method used is group dynamics, which involves fun activities to stimulate the cognitive and social of the elderly. This activity is expected to increase social interaction, sensory stimulation, and improve the cognitive function of the elderly. The implementation of therapy was carried out involving 60 elderly people, with stages that included orientation, work, and termination. Evaluations showed that 60% of participants actively participated in laughter and guess therapy, as well as being able to express their feelings. This program has shown success in improving the quality of life of the elderly by encouraging them to be more active and social. In conclusion, TAK can be an effective solution to improve the quality of life of the elderly through physical and cognitive stimulation. It is recommended that this program be carried out regularly to maintain the memory and social health of the elderly.